2013
DOI: 10.3762/bjoc.9.44
|View full text |Cite
|
Sign up to set email alerts
|

A peptidic hydrogel that may behave as a “Trojan Horse”

Abstract: SummaryA physical hydrogel prepared with the low-molecular-weight hydrogelator (LMWHG) CH2(C3H6CO-L-Phe-D-Oxd-OH)2 and water/ethanol mixture was applied as a potential “Trojan Horse” carrier into cells. By SEM and XRD analysis we could demonstrate that a fibrous structure is present in the xerogel, making a complex network. The gelator is derived from α-amino acids (Thr, Phe) and a fatty acid (azelaic acid) and is biocompatible: it was dosed to IGROV-1 cells, which internalized it, without significantly affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…[19] These molecules cause al ocal constraint in the pseudopeptide chain that favours the formationo fs econdary structures, [20][21][22] fibers [23][24][25] and gels. [26][27][28] Thus we prepared hydrogels based on Fmoc-l-Phe-d-pGlu-OH to test them for the adsorptiono fM ethylene Blue (MB), ac ationic dye, and Eosin Y( EY), an anionic dye, as these molecules may be used as model pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…[19] These molecules cause al ocal constraint in the pseudopeptide chain that favours the formationo fs econdary structures, [20][21][22] fibers [23][24][25] and gels. [26][27][28] Thus we prepared hydrogels based on Fmoc-l-Phe-d-pGlu-OH to test them for the adsorptiono fM ethylene Blue (MB), ac ationic dye, and Eosin Y( EY), an anionic dye, as these molecules may be used as model pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Over the years, a large number of building blocks have been identified as LMWGs, but their rational design and the prediction of their behaviour is still a challenge. Derivatives of the l-Phe-d-Oxd moiety may behave as fibre-like materials, [8] interact with lipid membranes, [9] form supramolecular helices [10] or be excellent organo-and hydrogelators, [11] also in the presence of metal ions. Derivatives of the l-Phe-d-Oxd moiety may behave as fibre-like materials, [8] interact with lipid membranes, [9] form supramolecular helices [10] or be excellent organo-and hydrogelators, [11] also in the presence of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…In Chapter we demonstrated that some bolamphiphiles of the series 11a–d and 12a–d efficiently gelate solutions containing metal ions . Thus, if these materials are biocompatible, they may behave as “Trojan horses” and carry drug molecules into the cells . To check the ability of these gels to cross the membrane barrier of ovarian cancer cells line IGROV‐1 by confocal laser scanning microscopy, some fluorescent hydrogels have been prepared using the bolamphiphic gelator 9b together with compounds 3.1, 24 , 25 , and 26 , all containing the fluorescent dansyl group (Figure ).…”
Section: Applicationsmentioning
confidence: 99%
“…[44] Thus, if these materials are biocompatible, they may behave as "Trojan horses" and carry drug molecules into the cells. [55,56] To check the ability of these gels to cross the membrane barrier of ovarian cancer cells line IGROV-1 by confocal laser scanning microscopy, some fluorescent hydrogels have been prepared using the bolamphiphic gelator 9b together with compounds 3.1, 24, 25, and 26, all containing the fluorescent dansyl group (Figure 16). Some images of confocal laser scanning micrographs of IGROV1 cells exposed to different hydrogels are shown in F IG UR E 1 7 Confocal laser scanning micrographs of IGROV1 exposed to different hydrogels using 9b as gelator, doped by little amount of the dansyl containing compounds 24, 25, and 26.…”
Section: Bolaamphiphilic Lmwgs As Trojan Horsesmentioning
confidence: 99%
See 1 more Smart Citation